Potentiometric study of equilibrium constants of a novel triazine–thione derivative and its stability constants with $Hg^{2+},Cu^{2+},Ni^{+2},Pb^{2+},$ and $Zn^{2+}$ metal ions in ethanol and water mixed - Polat, Fatih; Atabey, Hasan; Sari, Hayati; Çukurovalı, Alaaddin (My University, 2013)
The deprotonation constants of 5-hydroxy-5,6-di-pyridin-2-yl-4,5-dihydro-2H-[1,2,4] triazine-3-thione (HPT) and the stability constants of its $Hg^{2+},Cu^{2+},Ni^{+2},Pb^{2+},$ and $Zn^{2+}$ ion complexes were studied in 20% ethanol and water mixed at 25 ± 0.1 ◦C and ionic strength (I) of 0.1 M supported by NaCl. Four pKa values of HPT were determined: 3.58, 6.30, 9.23, and 9.69. In various pH conditions, the different complex forms were formulated as ML, MHL, $MH_2$ L, $MH_3$ L, $MH_4$ L, and $MH_{-2}$L between $Hg^{2+},Ni^{2+},Cu^{+2},Pb^{2+},$ and $Zn^{2+}$ ions and HPT. According to the potentiometric and spectrophotometric results, the HPT and $Hg^{2+}$ combination formed a selective and highly stable complex at pH 7.
Keywords: Kimya; Tıbbi